A method for obtaining efficient UE(s2)‐optimal two‐level supersaturated designs. Issue 1 (16th July 2021) - Evangelaras, Haralambos
Abstract : In this paper, we describe a method that can be used to obtain U E ( s 2 )‐optimal two‐level supersaturated designs. A major advantage of the proposed approach is the information it provides on the correlation structure of the generated U E ( s 2 )‐optimal supersaturated design and on the pairs of its orthogonal (or nearly orthogonal) columns. Therefore, it can be used to further distinguish between competitive U E ( s 2 )‐optimal designs. Examples are given to illustrate the usefulness and the flexibility of the proposed method.